Exploring the relationship among personal competence, resilience and response agility: the mediate effect of personal strength. - Vale, João Walter Saunders Pachêco do (2021)
Identifying the most suitable project manager to lead a project is a necessity in many organizations.The purpose of this thesis was to analyze the relationship between resilience and the personal Competences of project managers. This thesis was developed in the thesis model by scientific articles, more precisely, four articles were developed, 1 published, 2 submitted and one in the submission phase. The research methods used were systematic literature review, content analysis of employment opportunities, multi-case study and survey, so qualitative and quantitative approachs were used. The systematic literature reviews allowed the definition of the theme, the identification of the main variables and supported the construction of the theoreticalconceptual model of this thesis. The case study made it possible to explore the process of selecting project managers and developing their competences, this stage involved both semi-structured interviews and documentary analysis. Finally, a model was developed based on the understanding of resilience and personal competence treated in the literature reviews and the confirmatory stage was carried out through a survey. The survey was answered by 136 experienced professionals in the area of project management. The data collection instrument was a questionnaire, and the results of this collection were treated using the structural equation model (SEM - Structural Equation Model), with the estimation of partial least squares (PLS - Partial Least Square), for that the Sotware Smart PLS v3.0 was necessary. The Resilience construct was split into two elements, Resilience Personal Strength and Resilience ResponseAgility and 3 hypotheses were confirmed, Resilience Personal Strength and Resilience Response Agility have a positive influence on Personal Competences and Resilience Personal Strength has a positive influence on Resilience Response Agility that results an indirect influence also on Personal Competences.